Representasi Makna Harapan Pada Video Klip BTS "Permission to Dance" (Analisis Semiotika Roland Barthes) - Dina Sudarmika; Herlia Syafitri; Abdul Haris (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
ABSTRACT This research discusses the representation of expectations contained in bts' "Permission to Dance" video clip. The purpose of this study is to reveal how the representation of expectations conveyed by BTS on the "Permission to Dance" video clip is denotative, connotative, and mythical. The benefits of this research the author hopes to make a theoretical contribution as a reference for future research that will take the same concepts, theories, and methodologies as this research academically. for the community, this research is expected to be useful for the community, in order to have a more open view in facing difficulties with good and positive expectations to welcome the future. The research method used to analyze the "Permission to Dance" video clip is content analysis using a qualitative approach with semiotic analysis in the perspective of Roland Barthes.. The data collection technique uses documents in theform ofvideo clips. The results ofthisstudy show that there is a meaning of hope in BTS's "Permission to Dance" video clip. Finally, the author can conclude that the signs of hope contained in BTS' "Permission to Dance" video clip are flying purple balloons, divination magazines, removing masks, and dance movements. Keywords: Semiotics, Semiotics of Roland Barthes, Representation of Meaning